Fostering the Practice and Teaching of Statistical Consulting among Young Statisticians in Africa - Awe, Olushina Olawale (2014)
Statistical Consulting is unarguably one of the most challenging and rewarding aspects of statistics. It is both an art and a science because it involves both statistical and non-statistical skills. This article considers the usefulness of statistics, importance of statistical consulting and stresses the need to improve the practice of statistical consulting among young statisticians in Africa by including it in the curriculum of statistics programs in all African Universities and institutions of higher learning. The need to establish a statistical consulting unit in all the universities in Africa, whose activities will include providing advice for researchers on a full range of topics including statistical procedures for experiments, statistical and bio-mathematical modeling, statistical computing, and interpretation of results, is also proposed.